Characteristics of Carbon Monoxide Oxidization in Rich Hydrogen by Mesoporous Silica with TiO2 Photocatalyst. (24th November 2010) - Nishimura, Akira; Yamano, Yutaka; Hisada, Tomokazu; Hirota, Masafumi; Hu, Eric
Abstract : Hydrogen (H2 ) is normally used as the fuel to power polymer electrolyte fuel cell (PEFC). However, the power generation performance of PEFC is harmed by the carbon monoxide (CO) in the H2 that is often produced frommethane (CH4 ). The purpose of this study is to investigate the experimental conditions in order to improve the CO oxidization performance of mesoporous silica loaded with TiO2 . The impact of loading ratio of TiO2 and initial concentration ratio of O2 to CO on CO oxidization performance is investigated. As a result, the optimum loading ratio of TiO2 and initial concentration ratio of O2 to CO were 20 wt% and 4 vol%, respectively, under the experimental conditions. Under this optimumexperimental condition, the CO in rich H2 in the reactor can be completely eliminated from initial 12000 ppmV after UV light illumination of 72 hours.